Efektifitas Pijat Bayi Dalam Mengurangi Frekuensi Diare Pada Bayi Usia 6 – 24 Bulan - Berliana Irianti; Nur Israyati (Jurnal Kesehatan Ilmiah Aufa Royhan, 2024)
Diarrhea is still a world health problem, especially in developing countries, diarrhea is the number one cause of death among toddlers throughout the world every year. Trend Evidence Based Practice (EBP) is an alternative and new method for providing care. Diarrhea massage is a touch to the baby's body that is given to treat diarrhea and reduce the frequency of defecation, because massage can improve nerves and the process of absorbing food. The type of research carried out was Quasi experimental with the one group pretest posttest method. Sampling in this study used a non-random sampling technique and purposive sampling. Data analysis used univariate and bivariate using SPSS. The statistical test for this research uses the Wilcoxon test. Baby massage is effective in reducing the frequency of diarrhea in toddlers. This can be seen in the mean value before the massage was 6.32 and after the massage there was a decrease in the frequency of diarrhea, namely with a mean of 2.64. There is a need for skills training for health workers in managing diarrhea quickly and effectively in reducing mortality and morbidity rates caused by diarrheal diseases and using complementary therapies such as baby massage as an alternative management of diarrhea.